Evaluation of the Effectiveness of Dynamic Neuromuscular Stabilization Training in Children Diagnosed with Lower Urinary Tract Dysfunction and Comparison with EMG Biofeedback Treatment: A Pilot Study - Nacar, Emine; Suner Keklik, Sinem; Elmas, Ahmet Taner (Urology Journal, 2025)
Purpose: This study was designed to evaluate the effectiveness of dynamic neuromuscular stabilization (DNS) training in children with non neurogenic lower urinary tract dysfunction (LUTD) and compare it with biofeedback (BF) treatment. Materials and Methods: A total of 15 participants aged 6–15 years with non neurogenic LUTD were divided into three groups: Group I, DNS exercise training; Group II, BF training; and Group III, DNS plus BF training. Dysfunctional Voiding and Incontinence Scoring System (DVISS) scores, uroflowmetry parameters, uroflow curve, post void residual (PVR) values, and deep trunk muscle strength were evaluated at baseline and at 4, 8, and 12 weeks after treatment. Results: Total DVISS scores significantly decreased after 12 weeks in Groups I and III, while Group II showed significant decreases at 4 and 8 weeks (P < .05). Improvements in deep trunk muscle strength at 4 and 8 weeks were significantly greater in Groups I and III than in Group II (P < .05). In Group I, average flow rate increased at 4 weeks and flow time decreased at 12 weeks (P < .05). PVR decreased significantly at 12 weeks in Group I and at 8 weeks in Group III (P < .05). Conclusion: DNS and BF training are effective in improving symptoms in patients with non neurogenic LUTD; however, groups receiving DNS exercises were superior for several parameters.